Trade issues affecting disaster response - Michael Roberts; Nazia Mohammed (World Trade Organization (WTO), 2017)
The frequency, severity and economic impact of natural disasters are growing. Import surges resulting from disaster-response efforts can highlight underlying structural failings in the border clearance regimes of disaster-affected countries. Relief supplies, specialized personnel and agencies often face regulatory barriers affecting their entry and practice in disaster-affected environments. Against that background, the purpose of this working paper is twofold: it sets out to explore trade issues that can undermine effective disaster response, and then outlines how these trade issues might be addressed, including through implementation of the WTO Trade Facilitation Agreement as well as through technology-enabled services and the expansion of disaster risk insurance. The merits of further discussion of trade and natural disasters are also discussed.
Keywords: F13; J60; K33; 330; trade policy; disaster-response; WTO trade facilitation agreement